Redbanded Hairstreak, Calycopis cecrops (Fabricius) (Insecta: Lepidoptera: Lycaenidae) - Donald W. Hall; Jerry F. Butler (EDIS, 2002)
The redbanded hairstreak is a very attractive butterfly and is one of our most common hairstreaks throughout the southeastern United States in dry open woods and wooded neighborhoods. This document is EENY-108, one of a series of the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date August 1999. Reviewed May 2003.